Reconstructing a Socio-Trust-Based Branding Model for Rural Islamic Educational Institutions to Enhance Prospective Students’ Enrollment Interest - Faizatul Aliyah (CV. Laskar Karya, 2026)
This study is motivated by the low effectiveness of branding strategies for educational institutions in rural areas, which tend to focus on formal information delivery and have not yet succeeded in building social trust within the community. The study aims to develop a Socio-Trust Branding model as a strategic approach to increasing student enrollment interest. It employs a qualitative descriptive-exploratory approach conducted at Pondok Pesantren Sullam Safina. The research subjects include institutional managers, educators, students’ parents, and surrounding community members. Data were collected through interviews, observations, and documentation, and analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The findings indicate that current branding practices remain partial and have not optimally integrated social trust, informal communication (Word of Mouth), and community engagement. The proposed Socio-Trust Branding model consists of strengthening social trust, activating informal communication, enhancing community embeddedness, and reinforcing interpersonal relationships, which collectively contribute to building positive perceptions and increasing student interest. The novelty of this study lies in integrating social trust, community engagement, and informal communication into a contextual branding model. The implications suggest that branding strategies for rural educational institutions should prioritize social relationships and collective trust to achieve greater effectiveness and sustainability.